2017
DOI: 10.1186/s13048-017-0326-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dehydroepiandrosterone supplementation on ovarian response is associated with androgen receptor in diminished ovarian reserve women

Abstract: BackgroundDiminished ovarian reserve(DOR) is associated with female infertility and poor response to ovarian stimulation. Our objective was to assess the effect of dehydroepiandrosterone(DHEA) on DOR women and to explore whether the improvement of ovarian response after DHEA supplementation was dependent on the expression levels of androgen receptor(AR).MethodsA prospective cohort study was performed in the Department of Human Reproductive Medicine, Beijing Obstetrics and Gynecology Hospital during August 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 41 publications
3
29
0
4
Order By: Relevance
“…However, animal studies have clearly shown that androgens increase FSH receptor expression, and synergize with FSH to stimulate follicle growth and follicle responsiveness to FSH (Weil et al 1999, Wang et al 2001, Sen et al 2014. In support of this synergistic interaction, DHEA supplementation was reported to significantly increase protein and mRNA FSH receptor expression in preovulatory granulosa cells collected from POR patients (Hu et al 2017). Another potential mechanism by which androgen pre-treatment may mediate a beneficial effect is by maintaining follicle health.…”
Section: Current Implications and Future Directions From Basic Researmentioning
confidence: 98%
See 1 more Smart Citation
“…However, animal studies have clearly shown that androgens increase FSH receptor expression, and synergize with FSH to stimulate follicle growth and follicle responsiveness to FSH (Weil et al 1999, Wang et al 2001, Sen et al 2014. In support of this synergistic interaction, DHEA supplementation was reported to significantly increase protein and mRNA FSH receptor expression in preovulatory granulosa cells collected from POR patients (Hu et al 2017). Another potential mechanism by which androgen pre-treatment may mediate a beneficial effect is by maintaining follicle health.…”
Section: Current Implications and Future Directions From Basic Researmentioning
confidence: 98%
“…Studies have reported that DHEA administration has improved antral follicle numbers, oocyte retrieval numbers, fertilization rates, embryo implantation rates, embryo quality, clinical pregnancy rates and live birth rates in some women (observations from studies summarized in Table 2). However, there are also a noteworthy number of studies, including well-designed placebo-controlled randomized control trials (RCTs), which have reported no consistent improvement in any endpoints assessed after exposure of women to DHEA prior to ovarian stimulation (Artini et al 2012, Yeung et al 2014, Kara et al 2014, Vlahos et al 2015, Hu et al 2017, Narkwichean et al 2017, Li et al 2018.…”
Section: Dehydroepiandrosterone (Dhea)mentioning
confidence: 99%
“…For instance in prostate-derived LNCaP tumor cells, DHEA acts at the androgen receptor (AR) and beta estrogen receptor beta (ER-beta) at similar affinities, but the effects at ERbeta appear to be more physiologically relevant (100). In contrast, DHEA does appear to have demonstrable effects on AR mRNA expression in ovarian granulosa cells (101). Thus, the actions of DHEAS are unlikely to be sufficiently characterized as that of a weak androgen alone, and it is important to consider the specific tissue and/or organ involved.…”
Section: Igf-1 and Dhea/smentioning
confidence: 99%
“…23 – 28 The risk of infertility is higher after the age of 30, as the follicle reserve diminishes with age. 29 33 A large Norwegian study enrolled women diagnosed with and treated for HL, and reported that patients aged under 25 years had the same risk of infertility as the patients older than 30 years, but with delayed complications (15 vs 2 years). 34 …”
Section: Current Knowledge On Fertility and Hl Chemotherapymentioning
confidence: 99%